The Effect of Die Spacer on Retention and Fitting of Complete Cast Crowns - Anna Belsuzarri Olivera, DDS, PhD1 and Tetsuo Saito, DDS, DDSc2 (Journal of Prosthodontics, 2006)
This study evaluated the effect of die spacer on the fit and retention of complete cast crowns by using three different cements